Responding to the Needs and Challenges of Arts Entrepreneurs - Dianne Welsh; Tamaki Onishi; Ruth DeHoog; Sumera Syed (Artivate, 2014)
To address the call for examination of academic and professional approaches to arts entrepreneurship, we summarize the academic arts entrepreneurship programs in the State of North Carolina and conduct a pilot study with data gathered from arts entrepreneurs who attended the 5th annual Southern Entrepreneurship in the Arts Conference in Greensboro, North Carolina. Our review of the descriptive data reveals that arts entrepreneurs face a variety of needs and challenges, which are psychological (e.g., peer support) as well as technical (e.g., start-up skills). These findings suggest that, as prior literature stresses, arts entrepreneurship education programs should entail both the “entrepreneurship mindset” aspect and the “venture creation” aspect, so we advocate a holistic approach that combines both these perspectives with other related courses. We conclude, based on our exploratory study, that collaborative and flexible approaches, such as cross-campus programs for arts entrepreneurship education in higher education, could have beneficial outcomes for art entrepreneurs. Implications for future research are discussed.